The relationship between organizational learning culture, organizational citizenship behaviour, psychological empowerment and turnover intention / Amni Faiqah Abdul Razak - Abdul Razak, Amni Faiqah (Faculty of Business and Management, 2019)
This research study aims at the relationship of organizational learning culture, organizational citizenship behaviour, psychological empowerment and employee turnover intention at XYZ Company, a construction company in Melaka. This quantitative method is using a survey questionnaire to collect data. By using convenience sampling technique, 44 employees were sampled for the study among the XYZ Company’s employees. From SPSS version 2, multiple regression analysis showed that one out of three independent variables that is significant to turnover intention, which is, psychological empowerment whilst organizational learning culture and organizational citizenship behaviour does not. The findings of this study can be used by higher level positions in the company to justify their contributions in the company. By that, turnover may be reducing among the employees. Several implications from the research were discussed in details.